2007
DOI: 10.1021/es063004y
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls in Chinese Surface Soils

Abstract: Polychlorinated biphenyl (PCB) concentrations in surface soil samples (0-20 cm) from 52 sites (4 background, 39 rural, and 9 urban) across China in 2005 are presented. The average concentration of total PCBs among all the sites was 515 pg/g dry weight (dw), approximately one-tenth of that in global background soil in 1998. Differences of less than 1 order of magnitude were found between all background and rural sites, indicating a generally uniform distribution of PCBs in Chinese background/rural surface soil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
125
5
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(156 citation statements)
references
References 9 publications
(2 reference statements)
23
125
5
3
Order By: Relevance
“…The PCB levels were within the concentration range in soils recently reported from East, Northeast, and North China (average 1.07-35.5 ng/g) (Teng et al, 2008;Wang et al, 2008Wang et al, , 2010Wu et al, 2011;Zhang et al, 2007) and comparable to the PCB levels in the global background soil (average 5.41 ng/g) (Meijer et al, 2003). Nevertheless, the values in the present study were higher than the PCB concentrations (0.14-1.84 ng/g, average 0.52 ng/g) in soils across China (including urban, rural, and background soils) (Ren et al, 2007). The PCB homolog composition was similar to that in the Chinese technical PCB product but different from that in soils across China (Fig.…”
Section: Concentrations and Compositions Of Ocps And Pcbssupporting
confidence: 70%
See 1 more Smart Citation
“…The PCB levels were within the concentration range in soils recently reported from East, Northeast, and North China (average 1.07-35.5 ng/g) (Teng et al, 2008;Wang et al, 2008Wang et al, , 2010Wu et al, 2011;Zhang et al, 2007) and comparable to the PCB levels in the global background soil (average 5.41 ng/g) (Meijer et al, 2003). Nevertheless, the values in the present study were higher than the PCB concentrations (0.14-1.84 ng/g, average 0.52 ng/g) in soils across China (including urban, rural, and background soils) (Ren et al, 2007). The PCB homolog composition was similar to that in the Chinese technical PCB product but different from that in soils across China (Fig.…”
Section: Concentrations and Compositions Of Ocps And Pcbssupporting
confidence: 70%
“…tetra-, and di-PCBs constituted the majority of PCBs (Ren et al, 2007). These findings indicated that the soils in this region were subject to higher PCB pollution than most Chinese soils because of the intensive industrial activities in and around Shouguang region.…”
Section: Concentrations and Compositions Of Ocps And Pcbsmentioning
confidence: 79%
“…P 25 PCBs in soils ranged from 59 to 287 pg/g with an average value of 163 pg/g, These concentrations are comparable to the ones reported by Wang et al (2009) in soils from the Tibetan Plateau (mean value 186 pg/g) and lower than the PCB concentrations (424 pg/g) in soils from Chinese background areas (Ren et al, 2007), global background levels (5410 pg/g) (Meijer et al, 2003), and an Italian mountain near a regional industrial source (3600 AE 2300 pg/g) (Tremolada et al, 2008), whereas higher than those of Peru mountain (80 AE 140 pg/g) (Tremolada et al, 2008). The main congeners were tri-CBs and hexa-CBs, which accounted for 48.2% and 17.5% of P 25 PCBs, respectively.…”
Section: Concentrations Of Pcbs and Pbdessupporting
confidence: 67%
“…The main congeners were tri-CBs and hexa-CBs, which accounted for 48.2% and 17.5% of P 25 PCBs, respectively. A recent study also reported that di-and tri-CBs were the dominant congeners in soils from remote/farm region while hexa-CB and tri-CB were the main congeners of those from urban area in China (Ren et al, 2007). Seven indicator PCBs (including 52,101,118,153,138,and 180) were detected in all samples with concentration ranges of 0.2e151 pg/g, which accounted for 71%e 84% of P 25 PCBs.…”
Section: Concentrations Of Pcbs and Pbdesmentioning
confidence: 67%
“…These properties make it possible for PCBs to undergo long-range transport, and they pose global risks to human health and the environment (Liu et al 2009a;Meijer et al 2003;Ren et al 2007). The manufacture and use of commercial products containing PCBs were banned in most countries in 1973.…”
Section: Introductionmentioning
confidence: 99%